Habitat relationships of sun bears (Helarctos Malayanus) and an evaluation of non-invasive methods for estimating sun bear population size at Tabin wildlife reserve, Sabah, Malaysia - Tee, Thye Lim (2020)
The sun bear (Helarctos malayanus) has been classified as ‘Vulnerable’ by the IUCN due to habitat loss and poaching. Evaluating how bears respond to human-modified landscapes provides insights into their ecological requirements and survival in altered habitats. Live-capture and marking of sun bears are challenging because of low densities and logistic constraints. Hence, development of noninvasive sampling techniques for long-term population monitoring is crucial. We investigated habitat use of sun bear within Tabin Wildlife Reserve and tested the noninvasive sampling methods for estimating population size. Cameras were placed at 83 stations ≥ 1 km apart, each station was monitored for sun bear detection for an average of 60-days. We used generalized linear models to examine relationships between sun bear presence and habitat variables. We constructed 20 a priori model with different combinations of habitat covariates and used the second-order Akaike information criterion (AICc) to identify the most parsimonious model. We set-up 45 hair traps at baited stations to sample sun bear hair and chest-mark image. Trapping sites were spaced 1 km apart and equipped with one remote camera, revisited every 7-days for 4 consecutive weeks. The relative probability of sun bear presence was positively associated with distance to roads and elevation. Sun bears close to the reserve boundary were primarily active at night, whereas daytime activity was more common for bears in the interior of the reserve. We collected 30 hair samples and 15 chestmark images over 1,260 trap nights. Back-rubbing behavior resulted in the identification of six individual bears based on their chest-mark. Two individuals were recaptured eight times and twice, respectively. The tendency of sun bears to use higher elevations and maintain greater distances from roads may reflect selection of areas away from human disturbance. Sun bears near reserve boundaries may be more active at night to avoid human activities. The tree-taped hair trap design had a higher rate of success both chest-mark photography and hair snagging. Additional research is needed to improve the full potential of these methods for population monitoring of sun bears.